1999
DOI: 10.1159/000006616
|View full text |Cite
|
Sign up to set email alerts
|

The Ocular Morphology of the Southern Hemisphere Lamprey Geotria australis Gray, with Special Reference to Optical Specialisations and the Characterisation and Phylogeny of Photoreceptor Types

Abstract: This paper describes the ocular morphology of young adults of the southern hemisphere lamprey Geotria australis, the sole representative of the Geotriidae, and makes comparisons with those of holarctic lampreys (Petromyzontidae). As previously reported for the holarctic lamprey Ichthyomyzon unicuspis [Collin and Fritzsch, 1993], the lens of G. australis is non-spherical and possesses a cone-shaped posterior that may be capable of mediating variable focus. The avascular retina of G. australis is well differenti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
57
2

Year Published

2002
2002
2020
2020

Publication Types

Select...
8

Relationship

6
2

Authors

Journals

citations
Cited by 48 publications
(61 citation statements)
references
References 49 publications
2
57
2
Order By: Relevance
“…These findings were later refuted by several authors who identified conelike receptors in the eyes of cyclostomes, i.e. lampreys (Ö hman 1971;Dickson & Graves 1979;Govardovskii & Lychakov 1984;Tonosaki et al 1989;Collin et al 1999;Collin & Trezise 2004), but the characterization and distinction of rods and cones in the early vertebrates is not at all clear and has been the subject of great debate for over 150 years (Crescitelli 1972).…”
Section: Evolution Of Early Photoreceptors (A) Rods or Cones?mentioning
confidence: 97%
“…These findings were later refuted by several authors who identified conelike receptors in the eyes of cyclostomes, i.e. lampreys (Ö hman 1971;Dickson & Graves 1979;Govardovskii & Lychakov 1984;Tonosaki et al 1989;Collin et al 1999;Collin & Trezise 2004), but the characterization and distinction of rods and cones in the early vertebrates is not at all clear and has been the subject of great debate for over 150 years (Crescitelli 1972).…”
Section: Evolution Of Early Photoreceptors (A) Rods or Cones?mentioning
confidence: 97%
“…For light microscopy, enucleated eyes were immersion fixed in 4% paraformaldehyde in 0. cacodylate buffer (pH·7.4) and embedded in araldite before being sectioned on an LKB rotary ultramicrotome (Collin et al, 1999). Ultra-thin sections were stained with lead citrate and uranyl acetate, and examined on either a Phillips 410 or a Phillips CM10 transmission electron microscope set at 80·kV (Phillips Inc., Eindhoven, The Netherlands).…”
Section: Light and Electron Microscopymentioning
confidence: 99%
“…In both downstream and upstream migrant phases of the adult lifecycle of the pouched lamprey, Geotria australis, the sole representative of the Geotriidae family of southern hemisphere lampreys, five types of photoreceptor have been identified (Collin et al 1999(Collin et al , 2003aCollin & Trezise 2004;Fig. 2B).…”
Section: Visual Sampling Of An Ancient Aquatic Landscapementioning
confidence: 99%
“…However, an intracellular yellow/orange photostable pigment is present in the myoid and ellipsoidal regions of at least three of the five photoreceptor types in the southern hemisphere lamprey G. australis (Collin et al 1999;Collin & Trezise 2004;Figs 2B,3A,B). This pigment, which is also retained within one of the cone photoreceptor types in N. forsteri (Bailes et al 2006;Figs 2D, 3C), acts as a spectral filter, which absorbs wavelengths below approximately 550 nm (Collin et al 2003a).…”
Section: Early Mechanisms For Enhancing Visionmentioning
confidence: 99%
See 1 more Smart Citation